The study on Nannochloropsis oculata and Chlorella Vulgaris microalgae freely suspended technique for heavy metal removal in Palm Oil Mill Effluent - Vengadesperumal, Bavithrasindhu; Nor Faizah binti Razali (Progress in Engineering Application and Technology, 2023)
Wastewater recycling provides significant environmental benefits. Treating wastewater with microalgae is environmentally friendly. The main objective of the research is to compare the effectiveness of using microalgae in removing heavy metals in POME. Two different types of microalgae are used which are Nannochloropsis oculata and Chlorella vulgaris. From the data, it shows that both the microalgae can treat the POME in their respective concentration. Immobilization of algae can solve the problem POME remediation and bioenergy cogeneration.